(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Fe doped Mn2O3 nanoparticles were synthesized by the microwave-assisted method and synthesized sampleswere further annealed at 5000 C and the samples were subjected to analyze structural and Phase Analysisproperties. The structural properties of the nanoparticles were characterized by using X-ray diffractometry. XRDpattern revealed that the existence of Mn2O3 with cubic structure and Mn-doped Fe is a rhombohedral latticestructure. The Raman analysis confirms the phase formation of the prepared samples.